Penggunaan Terapi Musik Instrumental untuk Mengurangi Kecemasan Pasien Pada Saat Pencabutan Gigi Permanen di Puskesmas - Asridiana, Asridiana; Liasari, Ira; Abdullah, Nurwiyana; Zalsabila, Nabila (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2023)
Dental and oral health is one of the supporting factors for public health. Tooth extraction procedures are the most common cause of dental anxiety. One way to reduce dental anxiety is through nonpharmacological interventions. Music therapy is an example of nonpharmacological intervention. The purpose of this study was to determine the effect of instrumental music therapy on the patient's anxiety level during permanent tooth extraction at the Community Health Center. This type of research is a quasi-experimental research group pre-test and post-test design. The sampling technique used was consecutive sampling where the samples taken were patients with indications for tooth extraction who came to visit the Batang Community Health Center as many as 30 patients. Data analysis in this study used a paired t-test to see the difference. The results of this study found significant differences in the anxiety levels of patients who were not given music therapy (p>0.12) and those who were given music therapy (p>0.01). This study concluded that there was no significant effect of anxiety levels before and after tooth extraction in patients who did not receive music therapy. Whereas for patients who received music therapy there was a significant influence of anxiety levels before and after tooth extraction.